Hyperledger frameworks with a special focus on Hyperledger Fabric / Программная платформа Hyperledger с особым акцентом на блок-схему Hyperledger Fabric / Radna okruženja Hyperledger sa posebnim osvrtom na Hyperledger Fabric - Marija S. Krstić (University of Defence in Belgrade, 2020)
Introduction/purpose: The Blockchain market is a developing market, and many industries are increasingly aware of the importance of having and implementing Blockchain due to changing business conditions. After an introductory consideration of the Blockchain concept, the article focuses on the projects under the Linux Hyperledger Initiative, with particular reference to Hyperledger Fabric, notably on the concepts, architecture, organizational focus, private channels and smart contracts, as well as flow of transactions in the Hyperledger Fabric network. In the last, practical part of the paper, we presented a simulation of a business network and created a simple application for money exchange using the Hyperledger Fabric framework. The aim of the paper is to present the Hyperledger frameworks and highlight all the details of Hyperledger Fabric in order to determine whether its application in practice is justified. Methods: Basic methods (analysis, synthesis, deduction, induction, concretization, generalization) as well as general-scientific methods (analytical-deductive and comparative) were used. Results: All relevant features of Hyperledger Fabric were considered, a blockchain business network based on it was built, and an application for cash exchange through the network was created. Conclusion: Hyperledger Fabric is the most comprehensive and the most flexible Hyperledger framework with the largest number of use cases. / Введение/цель: Развивающийся рынок блокчейнов с каждым днем становится все интереснее для многих отраслей, которые вследствие изменения условий ведения бизнеса, стали лучше понимать насколько важно иметь и пользоваться блокчейнами. После вступительного ознакомления с концепцией Blockchain в статье представлены проекты в рамках инициативы компании Linux Foundation, с особым акцентом на деятельность Hyperledger Fabric ее концепциях, архитектуре, организационной направленности, частных каналах и умных-контрактах, а также на потоке транзакций в сети Hyperledger Fabric. В последней практической части статьи представлены бизнес-симуляция и разработанное простое приложение для обмена денежных средств с помощью системы Hyperledger Fabric. Целью данной статьи является представление рабочих условий Hyperledger и выявление всех деталей Hyperledger Fabric, для того чтобы можно было понять насколько применение системы Hyperledger на практике является обоснованным. Методы: В работе применялись основные методы (анализ, синтез, дедукция, индукция, конкретизация, обобщение), а также общенаучные методы (аналитико-дедуктивный и сравнительный). Результаты: Были рассмотрены все релевантные характеристики Hyperledger Fabric, создана бизнес-сеть блокчейнов и разработано приложение для обмена денежных средств в сети. Выводы: Hyperledger Fabric – это самая масштабная и гибкая Hyperledger программная платформа с наибольшим количеством пользователей.